2021
DOI: 10.1088/1674-1137/ac28f3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the favored alpha-decay half-lives of deformed nuclei

Abstract: A systematic study on the α-decay half-lives of nuclei in the range is performed by employing various versions of proximity potentials. To obtain more reliable results, deformation terms are included up to hexadecapole ( ) in the spherical-deformed nuclear and Coulomb interaction potentials. First, the favored α-decay processes in this region are categorized as even-even, od… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…For and , the deformation around the region with and may result in large deviations for these two nuclei [78,88,89]. For , , , and in these excited state, the corresponding experimental data may have Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For and , the deformation around the region with and may result in large deviations for these two nuclei [78,88,89]. For , , , and in these excited state, the corresponding experimental data may have Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, multiple models have been proposed to study α decay, including effective liquid drop model [38,39], fission-like model [52], generalized liquid drop model (GLDM) [48,49], density dependent M3Y (DDM3Y) effective interaction [43,44], and several others [58][59][60][61]. Furthermore, many empirical formulas have been adopted to investigate α decay based on the Geiger-Nuttall (G-N) law and/or the quantum tunneling effect [67], such as the universal decay law (UDL) [68,69], Viola-Seaborg-Sobiczewski (VSS) formula [70], Royer formula [45], Hatsukawa formula [71], Deng-Zhang-Royer formula (DUR) [72], Sobiczewski-Parkhomenko (SP) formula [73], and so forth [74][75][76][77][78][79][80][81][82]. In 2020, Bayrak proposed a phenomenological harmonic oscillator potential model (HOPM) [83] based on the Wentzel-Kramers-Brillouin (WKB) method and Bohr-Sommerfeld quantization condition.…”
Section: Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research shows that the deformation has a certain influence on the calculation of α decay half-lives [46,47,51]. Recently, Hassanzad et al [52] systematically studied the favored α decay half-lives of deformed nuclei with 93 Z 118 using deformed Coulomb and proximity potential model. Their results indicated that the deformation has a certain effect on α decay half-lives.…”
Section: Introductionmentioning
confidence: 99%